Outcomes of biliopancreatic EUS in patients with surgically altered upper gastrointestinal anatomy: a multicenter study - Lorenzo Brozzi; Maria Chiara Petrone; Jan-Werner Poley; Silvia Carrara; Luca Barresi; Carlo Fabbri; Mihai Rimbas; Claudio De Angelis; Paolo Giorgio Arcidiacono; Marianna Signoretti; Laura Lamonaca; Ilenia Barbuscio; et al. (Endoscopy International Open, 2020)
Background and study aims Little is known about outcomes of biliopancreatic endosonography (EUS) in patients with surgically altered upper gastrointestinal (gastrointestinal) anatomy. We aimed to assess the rate of procedural success and EUS-related adverse events (AEs), according to post-surgical anatomies. Patients and methods Retrospective study including patients with post-surgical altered upper gastrointestinal anatomy who underwent EUS for evaluation of the biliopancreatic region between January 2008 and June 2018 at eight European centers. Results Of 242 patients (162 males, mean age 66.4 ± 12.5), 86 had (35.5 %) Billroth II, 77 (31.8 %) pancreaticoduodenectomy, 23 (9.5 %) Billroth I, 19 (7.9 %) distal esophagectomy, 15 (6.2 %) total gastrectomy, 14 (5.8 %) sleeve gastrectomy, and eight (3.3 %) Roux-en-Y. Sleeve gastrectomy, Billroth I, and pancreaticoduodenectomy were associated with high rates of success (100 %, 95.7 %, and 92.2 %, respectively). Visualization of the head of the pancreas was significantly impacted by total gastrectomy, Billroth II, and Roux-en-Y (success rates 6.7 %, 53.7 %, and 57.1 %, respectively). Examination of the pancreatic body and tail was impaired in esophagectomy and total gastrectomy (82.4 % and 71.4 %, respectively). Technical success and diagnostic accuracy of EUS-guided tissue acquisition (EUS-TA) was 78.2 % and 71.3 % (95 % CI, 60.6–80.5), respectively. Four (1.6 %) AEs were observed: one mucosal tearing in a Billroth II patient, one cardiac arrest in a distal esophagectomy patient, one bleed after EUS-TA in a Billroth I patient, and one acute pancreatitis after EUS-TA in a sleeve gastrectomy patient. Conclusions The yield of bilio-pancreatic EUS is dependent on lesion location and surgery type. Before considering EUS in these patients, one must carefully consider whether the lesion may be approachable by EUS.